LANGUAGE AND IDENTITY - Mirzaarabova Umida Iqboljon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In the first place, Language is an essential aspect of human communication and plays a crucial role in shaping someone’s identity. Our use of language reflects and influences our cultural, ethnic, national, and personal identities. It is through language that we express our thoughts, emotions, and experiences, and it’s a key element in how we connect with others and form social bonds.Therefore, This research article will explore the multifaceted relationship between language and identity, examining how language acquisition, variations, gender, minority status, and power dynamics contribute to the construction of one’s identity.